If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + 8m = 6m Combine like terms: 3m + 8m = 11m 11m = 6m Solving 11m = 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. 11m + -6m = 6m + -6m Combine like terms: 11m + -6m = 5m 5m = 6m + -6m Combine like terms: 6m + -6m = 0 5m = 0 Divide each side by '5'. m = 0 Simplifying m = 0
| 6x-8+3x=12x+8 | | 2x+10+2x-22=3x-18 | | .4(x+2.4)=2.96 | | (4x+9)+(2x-12)= | | 27x-36-14x+63=300 | | 4.5(x-9)=-25 | | 19-7m=14-6m | | 3/16-1/4 | | 5t^2+t=42 | | 2x-4(3x+1)-5= | | 3x-10+x+15=25 | | 11x-14=3x-14 | | x-1/x^3+2x | | N+17=14+3 | | -6+-12+-10+25= | | (x-3)squared=25 | | 3x^2+9=x^2+27 | | (x-3)/2=25 | | 6x^3-x^2-2x=0 | | 5x/2+12=-8 | | 5g+2g=7g | | 6-7g=-8 | | 6x+10y=50 | | x^3-9x^2+22x-15=0 | | 3n^2-5=0 | | 34-3w=25 | | 8x(8x-7)+-8x(9x-8)= | | 4-1/2 | | -50+87x=-75x^2-8x | | 8m^2+5m+4=7+3m | | 1/2*1/4 | | u+12u+17=0 |